Improving Demand and Supply Balance in a Closed-Loop Supply Chain : A Case Study in a Dynamic Reuse Spare Part Business - Tervo, Tomi (My University, 2023)
Many companies have adopted closed-loop supply chain (CLSC) systems in pursuit of greener operations through reuse product offering. Contrary to traditional forward supply chains, CLSCs combine both supply chain directions, forward and reverse. As well, the CLSC incorpo-rates circular manufacturing process into the loop, such as repairing, refurbishing, or reman-ufacturing. The combination of multiple simultaneous processes leads to added complexity in a circular system. This results in a wide range of challenges faced by a CLSC. The CLSC pro-cess challenges present themselves as unbalanced demand for reuse products and supply for returning end-of-use cores. As a result, this study’s purpose was to identify the most critical challenges contributing to an unbalanced demand and supply. Also, the study aimed to pro-vide improvement proposals to improve the situation at the case company. To realise this purpose, the study followed the format of a qualitative case study with a maritime company Wärtsilä as the case company. The research data was collected using open interviews with eight key stakeholders involved in the case company’s CLSC. Data from the interviews was then transcribed and analysed with a thematic analysis method; categorising found challeng-es into challenge categories identified from the existing literature. To examine the most criti-cal CLSC challenges, the study performed a criticality analysis using Process Failure Mode & Effect Analysis (PFMEA). PFMEA assigned severity to each found challenge while also evaluat-ing the case company’s current methods for prevention and detection. The analysis resulted in 14 different challenge categories expected to contribute to unbalanced demand and sup-ply. Two new challenge categories, challenges with process knowledge and challenges with a missing seeding strategy, were added to the body of knowledge. Regarding criticality, seven challenge categories were found as critical. Critical challenges in reverse supply chain pro-cesses related to limited internal and external process knowledge and visibility of returning cores. Critical challenges in circular manufacturing processes related to low core availability, pull-ordering system, outdated inventory management practices, and a missing seeding strategy. Finally, the study proposed improvement proposals for the critical challenges that would result in more balanced demand and supply. These findings stress the individual needs of each CLSC system to perform in an optimal manner. The case company’s single source for cores created new challenges that were yet to be identified by the existing litera-ture. Also, the separation of critical challenges aids managers in focusing on the most critical ones in often problem-rich CLSCs.
Keywords: circular economy; reuse; spare parts; supply chains; inventory control; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management